Methylglyoxal-Induced Modifications in Human Triosephosphate Isomerase: Structural and Functional Repercussions of Specific Mutations - Ignacio de la Mora-de la Mora; Itzhel García-Torres; Luis Antonio Flores-López; Gabriel López-Velázquez; Gloria Hernández-Alcántara; Saúl Gómez-Manzo; Sergio Enríquez-Flores (Molecules)
Triosephosphate isomerase (TPI) dysfunction is a critical factor in diverse pathological conditions. Deficiencies in TPI lead to the accumulation of toxic methylglyoxal (MGO), which induces non-enzymatic post-translational modifications, thus compromising protein stability and leading to misfolding. This study investigates how specific TPI mutations (E104D, N16D, and C217K) affect the enzyme’s structural stability when exposed to its substrate glyceraldehyde 3-phosphate (G3P) and MGO. We employed circular dichroism, intrinsic fluorescence, native gel electrophoresis, and Western blotting to assess the structural alterations and aggregation propensity of these TPI mutants. Our findings indicate that these mutations markedly increase TPI’s susceptibility to MGO-induced damage, leading to accelerated loss of enzymatic activity and enhanced protein aggregation. Additionally, we observed the formation of MGO-induced adducts, such as argpyrimidine (ARGp), that contribute to enzyme inactivation and aggregation. Importantly, the application of MGO-scavenging molecules partially mitigated these deleterious effects, highlighting potential therapeutic strategies to counteract MGO-induced damage in TPI-related disorders.